Evaluation of the chemical interaction between carbon nanotubes functionalized with TGDDM tetrafunctional resin and hardener DDS - Edwards, E. R. [UNESP]; Kostov, K. G. [UNESP]; Botelho, E. C. [UNESP] (Elsevier, 2013)
In this work, the chemical interaction between carbon nanotubes (MWCNT) functionalized with acyl chloride (SOCl2) and polymer chain tetrafuncional N,N,N′,N′-tetraglycidyl-4,4′- diaminodiphenylmethane (TGDDM) and hardener 4,4′diaminodiphenyl sulfone (DDS) has been monitored by Fourier transform infrared spectroscopy (FTIR) with a attenuated total reflectance (ATR) coupled. MWCNT were obtained from the pyrolysis of a mixture of camphor and ferrocene into a oven. The functionalization process was done by oxidative treatment in order to incorporate carboxylic group over the walls of MWCNT, before to be used SOCl2. The functionalized carbon nanotubes were evaluated by X-ray photoelectron spectroscopy (XPS), Raman and transmission electron microscopy (TEM). Nanostructured composites were processed by using epoxy resin with MWCNT in varying percentages. In this work it was observed that different percentages of functionalized nanotubes modify the interaction between the composite matrix and curing agent, where can be observed that in specimens with content less than 1 wt% MWCNT the chemical bond occurs preferentially from the opening of the SO double bond of the hardener and when is used MWCNT content higher than 1 wt% there is little chemical interaction with the SO bond of the hardener and most MWCNT binds to amine. © 2013 Elsevier Ltd.
Keywords: A. Nano-structures; B. Chemical properties; B. Interface; D. Surface analysis; Attenuated total reflectance; Diaminodiphenyl sulfones; Diaminodiphenylmethane; Functionalization process; Functionalized carbon nanotubes; Functionalized nanotubes; Nanostructured composites; Transmission electron microscopy (TEM); Chemical bonds; Chemical properties; Chlorine compounds; Epoxy resins; Fourier transform infrared spectroscopy; Organometallics; Photoelectrons; Resins; Surface analysis; Transmission electron microscopy; X ray photoelectron spectroscopy; Multiwalled carbon nanotubes (MWCN)